124k views
3 votes
PLEASE HELP WITH THIS

PLEASE HELP WITH THIS-example-1
User Angs
by
5.9k points

2 Answers

4 votes

Answer:


33 - 2x = {x }^(2) + 2x + 1 \\ {x}^(2) + 4x - 32 = 0 \\ x = 8 \\ \\ x = 4

User Chris Magnussen
by
5.0k points
3 votes

Answer:

x = 4

Explanation:

(33-2x)^(1/2) = x + 1

33-2x = x^2 + 2x + 1 [square both sides]

x^2 + 2x + 1 - 33 +2x = 0

x^2 + 4x - 32 = 0

(x - 4)(x + 8) = 0

x = 4

User Steve Townsend
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.